120 Standardizing Consent Forms for Outpatient Urology Procedures. (19th August 2022) - Shrestha, S; Jiang, E; Sandhu, A; Pinnamaraju, P; Swallow, T; Pai, A
Abstract: Introduction: British Association of Urological Surgeons (BAUS) guidelines have provided comprehensive and standardized guidelines for urological procedures, including indications, benefits, risks involved, and alternatives. At our institution, currently, consent forms are handwritten resulting in generalized or incomplete information given to patients. Aim: To improve patient understanding of the procedures they are undergoing by providing standardized consent form stickers for procedures as per BAUS guidelines. Method: Single institution data were collected retrospectively for flexible cystoscopy, stent removal, transrectal ultrasonography (TRUS), and transurethral laser ablation (TULA). Consent forms compared to BAUS guidelines. A standardized consent form sticker for each procedure was developed in accordance with BAUS guidelines and reviewed via the trust's clinical governance process. Clinicians were educated in their use for future consenting. Results: Consent forms of consecutive patients over a two-month period were analyzed. The initial audit showed that the proportion of patients who had all risks included was 0% for flexible cystoscopy, 0% for TRUS, and 100% for stent removal. Common and rare, but serious risks were not mentioned in all cases. 100% of patients had all risks mentioned for TULA. After education on the consent process and the introduction of consent form stickers, all risks (100%) were mentioned for all procedures. Conclusions: It is imperative that patients are fully informed about the risks, indications, and alternatives of their treatment. Failure to provide this information in full may lead to unnecessary angst, morbidity, and litigation. Simple quality improvement projects can lead to measurable improvement in patient information.